Evaluation of Muscle microRNA Expression in Relation to Human Peripheral Insulin Sensitivity: A Cross-Sectional Study in Metabolically Distinct Subject Groups - Dahlmans, Dennis; Houzelle, Alexandre; Jörgensen, Johanna A.; Phielix, Esther; Lindeboom, Lucas; Hesselink, Matthijs K. C.; Schrauwen, Patrick; Hoeks, Joris (Frontiers in Physiology, 2017)
In recent years, several microRNAs (miRNAs) - post-transcriptional regulators of gene expression - have been linked to the regulation of peripheral insulin sensitivity. Many of these studies, however, have been conducted in cell or animal models and the few human studies available lack adequate measurements of peripheral insulin sensitivity. In the present study, we examined the expression of 25 miRNAs, putatively involved in (peripheral) insulin sensitivity, in skeletal muscle biopsies from extensively phenotyped human individuals, widely ranging in insulin sensitivity. To identify miRNAs expressed in skeletal muscle and associated with insulin sensitivity and type 2 diabetes, a comprehensive PubMed-based literature search was performed. Subsequently, the expression of selected miRNAs was determined by RT-qPCR using predesigned 384-well Pick-&-Mix miRNA PCR Panel plates in muscle biopsies from type 2 diabetes patients, non-diabetic obese/overweight individuals, lean sedentary individuals and endurance-trained athletes. In all subjects, peripheral insulin sensitivity was measured by hyperinsulinemic-euglycemic clamp. The literature search resulted in 25 candidate miRNAs, 6 of which were differentially expressed in human type 2 diabetes compared to non-diabetic obese/overweight individuals. In turn, four of these miRNAs, i.e. miRNA27a-3p (r=-0.45, p=0.0012), miRNA-29a-3p (r=-0.40, p=0.0052), miRNA-29b-3p (r=-0.70, p<0.0001) and miRNA-29c-3p (r=-0.50, p=0.0004) demonstrated strong negative correlations with peripheral insulin sensitivity across all four subject groups. We identified miR-27a-3p and all members of the miRNA-29 family as potential regulatory players in insulin sensitivity in humans. These miRNA’s may represent interesting novel targets for maintaining or improving insulin sensitivity.